When dad went on a date - Oldfield, Jenny; Farrow, Martina (Hodder Children's London, 2002)
This fourth book about Tiffany Little's diary focuses on her efforts to set her dad up on a date, as well as her friends efforts to get a celebrity DJ's autograph